Stacking defect‐induced electronic cloaking of confined states and Fano resonance in zero‐energy shifted bilayer graphene. Issue 5 (6th December 2016) - Daboussi, A.; Mandhour, L.; Jaziri, S.
Abstract : We show that a stacking defect or a shift has a striking effect on transport properties of bilayer graphene. The tunneling through a ballistic n–neutral–n junction of shifted bilayer graphene may result at normal incidence in a zero‐energy cloaking effect. States normally incident on the barrier are confined under it, depending on their pseudospin orientation. These confined states are perfectly decoupled from continuum states having the opposite pseudospin orientation. The barrier at normal incidence acts as a cloak for confined states. We also show a shift‐dependent asymmetric zero‐energy Fano resonance at near normal incidence arising from the interference between continuum and confined states. These zero‐energy cloaking effect and Fano resonance are unique since they are achieved due to the stacking defect. They do not exist in the same setup of perfectly Bernal‐stacked bilayer graphene.